A New Approach for the Synthesis of Miktoarm Star Polymers Through a Combination of Thiol–Epoxy "Click" Chemistry and ATRP/Ring‐Opening Polymerization Techniques. Issue 2 (23rd November 2018) - Gadwal, Ikhlas; Wadgaonkar, Prakash P.; Ichake, Amol B.; Mane, Shivshankar R.
ABSTRACT: A new approach was developed for synthesis of certain A3 B3 ‐type of double hydrophilic or amphiphilic miktoarm star polymers using a combination of "grafting onto" and "grafting from" methods. To achieve the synthesis of desired miktoarm star polymers, acetyl protected poly(ethylene glycol) (PEG) thiols ( M n = 550 and 2000 g mol −1 ) were utilized to generate A3 ‐type of homoarm star polymers through an in situ protective group removal and a subsequent thiol–epoxy "click" reaction with a tris‐epoxide core viz . 1, 1, 1‐tris(4‐hydroxyphenyl)ethane triglycidyl ether. The secondary hydroxyl groups generated adjacent to the core upon the thiol–epoxy reaction were esterified with α‐bromoisobutyryl bromide to install atom transfer radical polymerization (ATRP) initiating sites. ATRP of N ‐isopropylacrylamide (NIPAM) using the three‐arm star PEG polymer fitted with ATRP initiating sites adjacent to the core afforded A3 B3 ‐type of double hydrophilic (PEG)3 [poly( N ‐isopropylacrylamide)] (PNIPAM)3 miktoarm star polymers. Furthermore, the generated hydroxyl groups were directly used as initiator for ring‐opening polymerization of ε‐caprolactone to prepare A3 B3 ‐type of amphiphilic (PEG)3 [poly(ε‐caprolactone)]3 miktoarm star polymers. The double hydrophilic (PEG)3 (PNIPAM)3 miktoarm star polymers showed lower critical solution temperature around 34 °C. The preliminary transmission electron microscopy analysis indicated formation of self‐assembly of (PEG)3 (PNIPAM)3 miktoarm star polymer in aqueous solution. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 146–156 Abstract : An approach involving a combination of thiol–epoxy "click" reaction and atom transfer radical polymerization/ring‐opening polymerization methods for the synthesis of A3 B3 ‐type miktoarm star polymers was developed for the first time. The synthesis of double hydrophilic (PEG)3 (PNIPAM)3 and amphiphilic (PEG)3 (PCL)3, A3 B3 ‐type miktoarm star polymers was demonstrated.